Tunable and high quality factor Fano and toroidal dipole resonances in terahertz superconducting metamaterials - Siyu Duan; Jingbo Wu; Ze Shen; Yun Guan; Xiaoqing Jia; Caihong Zhang; Biaobing Jin; Lin Kang; Weiwei Xu; Huabing Wang; Jian Chen; Peiheng Wu (Materials Research Express, 2020)
We experimentally studied a series of terahertz (THz) metamaterials with asymmetric resonator structures made from superconducting niobium nitride or gold films. Fano and toroidal dipole resonances are excited in superconducting metamaterials and their quality factors are higher in comparison with those of gold samples. Superconducting samples possess good tuning behaviors for both Fano and toroidal dipole resonance frequencies due to the change of kinetic inductance under different temperatures. The superconducting samples also exhibit good slow light effect due to the sharp dispersion in transmission spectra. These tunable and low loss metamaterials possess great significance to the development of THz nonlinear and slow light devices.